2019
DOI: 10.1002/ar.24221
|View full text |Cite
|
Sign up to set email alerts
|

The Generation of Zebrafish Mariner Model Using the CRISPR/Cas9 System

Abstract: Targeted genome editing mediated by clustered, regularly interspaced, short palindromic repeat (CRISPR)/CRISPR‐associated nuclease 9 (Cas9) technology has emerged as a powerful tool for gene function studies and has great potential for gene therapy. Although CRISPR/Cas9 has been widely used in many research fields, only a few successful zebrafish models have been established using this technology in hearing research. In this study, we successfully created zebrafish mariner mutants by targeting the motor head d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…Remarkably, zebrafish and mammalian hair cells share many fundamental features at the cellular and molecular level (Coffin et al, ). Several genetic studies have demonstrated that molecules required by the auditory and vestibular system of zebrafish are also important in mice and humans (Nicolson, ; Yariz et al, ; Diaz‐Horta et al, ; Grati et al, ; Bensaid et al, ; Varshney et al, ; DeSmidt et al, ; Zou et al, ). The inner ear of mammals is encased in the bony labyrinth deep inside the temporal bone, which prevents the sensory hair cells from being easily accessed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Remarkably, zebrafish and mammalian hair cells share many fundamental features at the cellular and molecular level (Coffin et al, ). Several genetic studies have demonstrated that molecules required by the auditory and vestibular system of zebrafish are also important in mice and humans (Nicolson, ; Yariz et al, ; Diaz‐Horta et al, ; Grati et al, ; Bensaid et al, ; Varshney et al, ; DeSmidt et al, ; Zou et al, ). The inner ear of mammals is encased in the bony labyrinth deep inside the temporal bone, which prevents the sensory hair cells from being easily accessed.…”
Section: Resultsmentioning
confidence: 99%
“…With the advent of new transgenic and imaging technologies that allow the analysis of phenotypes in astonishing detail, the zebrafish will remain at the forefront of hearing research for many years to come. CRISPR/Cas9 can easily be used as a reverse genetics technique to verify gene function in zebrafish (Hwang et al, ; Jao et al, ; Zou et al, ; Shaw et al, 2017; Zou et al, ). Therefore, reverse genetics as well as forward genetics techniques can be used to deduce the genetic developmental pathway in zebrafish.…”
Section: Introductionmentioning
confidence: 99%
“…This series of in vitro studies is followed by a group of five papers that probe the behavior of stem cells in vivo , looking at their ability to treat hearing loss and ultrastructural character of stem cell‐initiated hair cell regeneration: that is, “Bone marrow stromal cells accelerate hearing recovery via regeneration or maintenance of cochlear fibrocytes in mouse spiral ligaments,” (Kada et al, ); “Effect of bone marrow‐derived mesenchymal stem cells on cochlear function in an experimental rat model,” (Mittal et al, ); “Transplantation and tracking of human umbilical cord mesenchymal stem cells labeled with SPIO in deaf pigs,” (Xu et al, ); “Ultrastructural characterization of stem cell‐derived replacement vestibular hair cells within ototoxin‐damaged rat utricle explants,” (Werner et al, ); and “Recent advancements in gene and stem cell‐based treatment modalities: potential applications in noise‐induced hearing loss” (Eshraghi et al, ). The next group of papers looks at three genetic studies in the lab utilizing zebrafish models to examine both gene expression and gene editing, along with a gene vector delivery safety study in mice and then pair of human clinical studies that probe impact of genetic hearing disorders: that is, “Transcriptosomic analyses of inner ear sensory epithelia in zebrafish,” (Yao et al ., ); “Zebrafish model for non‐syndromic x‐linked deafness, DFNX1 ,” (De Smidt et al, ); “The generation of zebrafish Mariner model using the CRISPR/Cas9 system,” (Zou et al, ); “Hearing preservation following repeated adenovector delivery,” (Pfannensteil et al, ); “Congenital middle ear malformation with common deafness gene mutational analysis: a review of 813 profound sensorineural hearing loss child patients,” (Dong et al, ); and “Relationships between type of patients’ genetic deafness and their cochlear implant performance levels” (Usami et al ., ). The last group papers are three laboratory studies that deal with mechanisms of implantation trauma‐related fibrosis, creation of a tympanic membrane wound healing model for testing stem cell therapy, and the results of testing the ability of a neuroprotective drug to protect and/or rescue injured olfactory neurons: that is, “TGFB‐1 and WNT signaling pathways collaboration associated with cochlear implantation trauma‐induced fibrosis,” (Bas et al, ); “Animal model for chronic tympanic membrane perforation,” (Langston et al, ); and “Acute N‐acetylcysteine administration ameliorates loss of olfactory neurons following experimental injury in vivo” (Goncalves and Goldstein, ).…”
mentioning
confidence: 99%